The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/6907172
|View full text |Cite|
|
Sign up to set email alerts
|

An Optimized Decision Method for Smart Teaching Effect Based on Cloud Computing and Deep Learning

Abstract: In order to improve the effect of intelligent teaching and give full play to the role of intelligent technology in modern physical education, in this paper, cloud computing and deep learning methods are used to comprehensively evaluate the teaching effect of colleges and universities, and calculate the evaluation effect and accuracy. Cloud computing and deep learning algorithm combine the teaching evaluation scale, teaching content, and characteristics to formulate teaching plans for different students and rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…The ZOA algorithm principle can be divided into five major stages, which are includes in given steps. (15) where, m denotes zebra population, n and j signifies number of population.…”
Section: F Optimization Using Zebra Optimization Algorithm (Zoa)mentioning
confidence: 99%
See 1 more Smart Citation
“…The ZOA algorithm principle can be divided into five major stages, which are includes in given steps. (15) where, m denotes zebra population, n and j signifies number of population.…”
Section: F Optimization Using Zebra Optimization Algorithm (Zoa)mentioning
confidence: 99%
“…The assessment technique is utilized to test planned volleyball player health assessment method, outcomes display that method is dependable. But investigational data is too little, not sufficiently considerable [15]. Yulin utilized bibliographic data techniques, mathematical statistical approaches, DT prediction methods to conduct statistical exploration data of 198 unemployed women from four areas [16].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%